Benefits of macroalgal blooms for the production of biofertilizers: macroalgal blooms to produce biofertilizers - Soto-Jimenez, Martin F.; Ochoa-Izaguirre, María Julia; Bojorquez-Mascareño, Elsa I. (Revista Mexicana de Ciencias Agrícolas, 2019)
In the present essay, an alternative for the production of biofertilizers is proposed based on the use of macroalgal blooms that are occurring in the coastal lagoons of Sinaloa. Coastal communities can obtain an economic benefit by properly harvesting part of the biomass resulting from such blooms. The extracted macroalgal biomass could be used to produce biofertilizers, with the following benefits: a) mitigate the ecological damage caused by macroalgal blooms to eutrophicized coastal ecosystems; b) the use of organic fertilizers in agricultural fields allows N and P to be recycled, thus avoiding the application of more synthetic fertilizers, which are primarily responsible for macroalgal blooms; c) in addition to containing biofertilizers based on macroalgae, N and P contain a set of micronutrients and substances with the potential to benefit crops and improve soils; d) it contributes to carbon sequestration and the reduction of greenhouse gases in the atmosphere; and e) economic benefits in the use of a raw material, nowadays, of low value or without commercial value. Such biofertilizers would be used to produce fruits and vegetables of the so-called organic, which have a high surplus value and their demand is increasing in Mexico and in the world. This is an alternative focused on the production of biofertilizers for use in organic agriculture and production of fruits of high economic value, which can be accredited as organic and at the same time, contribute to the improvement of soils and the state of health of coastal ecosystems